2021
DOI: 10.1038/s41598-021-91079-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of hemodynamic factors and progressive aortic dilatation following type A aortic dissection surgical repair

Abstract: Type A aortic dissection (TAAD) involves the ascending aorta or the arch. Acute TAAD usually requires urgent replacement of the ascending aorta. However, a subset of these patients develops aortic rupture due to further dilatation of the residual dissected aorta. There is currently no reliable means to predict the risk of dilatation following TAAD repair. In this study, we performed a comprehensive morphological and hemodynamic analysis for patients with and without progressive aortic dilatation following surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 49 publications
3
27
0
Order By: Relevance
“…Re-intervention in patients with progressive aortic dilatation after surgical repair of TAAD is typically based on aortic size and the rate of expansion. In our previous studies, a systematic examination of the flow patterns and hemodynamic factors in dissected aortas was performed, and possible links were identified between luminal pressure difference and the progression of aneurysmal dilatation ( Zhu et al, 2021 ; Zhu et al, 2022 ). This study presents FSI simulations of two repaired TAAD patients, and the results from the FSI simulations are comprehensively compared with the corresponding CFD results to evaluate the assumption of rigid aortic wall.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Re-intervention in patients with progressive aortic dilatation after surgical repair of TAAD is typically based on aortic size and the rate of expansion. In our previous studies, a systematic examination of the flow patterns and hemodynamic factors in dissected aortas was performed, and possible links were identified between luminal pressure difference and the progression of aneurysmal dilatation ( Zhu et al, 2021 ; Zhu et al, 2022 ). This study presents FSI simulations of two repaired TAAD patients, and the results from the FSI simulations are comprehensively compared with the corresponding CFD results to evaluate the assumption of rigid aortic wall.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown that higher pressure difference between TL and FL (PD TL-FL ) may be associated with progressive aortic dilatation in repaired TAAD ( Zhu et al, 2021 ; Zhu et al, 2022 ). However, one major limitation of these studies was that the CFD simulations were based on rigid wall assumptions and thereby assessing the effect of wall compliance on PD TL-FL is of particular interest in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, analysis of pressure values can be helpful in the study of aneurysmal dilatation and malperfusion 23 , 38 . A more recent study has shown the importance of TAWSS and pressure difference values between the TL and FL in the prediction of rapid aneurysmal expansion in the dissected aorta 39 , confirming the need for further measuring of hemodynamic metrics for the prediction of further progression and development of AD. Furthermore, a recent review has indicated the importance of CFD tools and hemodynamic features for risk assessment in AD patients, which can be used by clinicians 40 .…”
Section: Introductionmentioning
confidence: 85%